2020
DOI: 10.1109/jbhi.2020.2964072
|View full text |Cite
|
Sign up to set email alerts
|

Objective ADHD Diagnosis Using Convolutional Neural Networks Over Daily-Life Activity Records

Abstract: Attention Deficit/Hyperactivity Disorder (ADHD) is the most common neurobehavioral disorder in children and adolescents. However, its etiology is still unknown, and this hinders the existence of reliable, fast and inexpensive standard diagnostic methods. Objective: This paper proposes an end-to-end methodology for automatic diagnosis of the combined type of ADHD. Methods: Diagnosis is based on the analysis of 24 hour-long activity records using Convolutional Neural Networks to classify spectrograms of activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In addition, only body parts equipped with sensors can be recorded. The difference between accelerometers and actigraphy is that accelerometer analyzes the subject’s movements during normal daily activities and the recording time is limited by the power of battery [ 29 ], whereas actigraphy studies the subject’s sleep efficiency and the recording is limited by low sampling rate [ 30 ]. Regarding to infrared, the strength of infrared is noncontact without placing any type of sensor in the body of the subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only body parts equipped with sensors can be recorded. The difference between accelerometers and actigraphy is that accelerometer analyzes the subject’s movements during normal daily activities and the recording time is limited by the power of battery [ 29 ], whereas actigraphy studies the subject’s sleep efficiency and the recording is limited by low sampling rate [ 30 ]. Regarding to infrared, the strength of infrared is noncontact without placing any type of sensor in the body of the subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, using Recurrent Neural Networks, they analyzed the data that collected similarly and failed to find a significant difference between the ADHD group and the control group [ 18 ]. In the latest study, Amado-Caballero et al placed a triaxial accelerometer on the wrist and used CNN to analyze 24-h activity data [ 21 ]. The results obtained a mean sensitivity of up to 97.62%, a specificity of 99.52%, and an AUC value of over 99%.…”
Section: Discussionmentioning
confidence: 99%
“…This study followed the STARD statement (Standards for Reporting of Diagnostic Accuracy Studies [ 19 ]. The area under the receiver operating curve (ROC) of previous similar wearable devices was 0.9 or more at α = 0.05 (unilateral), β = 0.1, and a 1:1 ratio between groups [ 20 , 21 ]. The sample size was estimated using PASS15 software (NCSS LLC.,Kaysville, U.T., USA) and a minimum of 55 participants with ADHD and 55 controls were needed after considering a 10% of lost to follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, using the ABIDE dataset, which was based on rs-fMRI and deep neural network, ASD was distinguished from typically developing subjects [71]. Wireless Communications and Mobile Computing In addition, it was found that CNN algorithm was most efficient among all applied ML algorithms, and several studies have reported the rise in accuracy for ADHD diagnosis and examination by utilizing CNN with an accuracy range of between 90 ± 10 percent [55,[72][73][74][75][76][77][78]. Similarly, numerous studies were also conducted using CNN for ASD diagnosis and analyses showing a high accuracy rate > 70-90% [44,[79][80][81][82].…”
Section: Recent Machine Learning and Deep Learning Softwarementioning
confidence: 99%